Nanoencapsulation of Pelawan Stem Extract (Tristaniopsis merguensis Grifft.) Using Polycaprolactone (PCL) - Mahardika, Robby Gus; Shakila, Shania; Budi Kurniawan, Widodo; Amelia, Ririn (ALKIMIA, 2023)
Formulation of nanoencapsulation using variations in the mass of Pelawan stem extract at (A) 0.15; (B) 0.25; and (C) 0.35 g combined with the addition of 0.5% PCL (Polycaprolactone) and Tween 80. Based on the analysis, the resulting nanocapsule sizes were 559.2, 447.2, and 297.0 nm, respectively, indicating that the nanoencapsulation of Pelawan stem extract has achieved nanoscale dimensions. The polydispersity index (PI) values for Pelawan stem extract formulas A, B, and C were 0.645, 0.687, and 0.476, respectively. Formula C has a PI value of less than 0.5, indicating that nanocapsules in formula C are more uniform. Formula C was the best formulation, with the smallest size and lowest PI. The Pelawan stem extract, rich in phenolic compounds, packaged in nanocapsule form through a simple nanoencapsulation process, holds potential as a future nutraceutical product.